2015
DOI: 10.1002/2014jb011231
|View full text |Cite
|
Sign up to set email alerts
|

Brittle creep and subcritical crack propagation in glass submitted to triaxial conditions

Abstract: An experimental work is presented that aimed at improving our understanding of the mechanical evolution of cracks under brittle creep conditions. Brittle creep may be an important slow deformation process in the Earth's crust. Synthetic glass samples have been used to observe and document brittle creep due to slow crack‐propagation. A crack density of 0.05 was introduced in intact synthetic glass samples by thermal shock. Creep tests were performed at constant confining pressure (15 MPa) for water saturated co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 60 publications
(90 reference statements)
1
22
0
Order By: Relevance
“…Three standard samples were chosen to test the experimental setup and procedure: (1) a synthetic glass sample made of amorphous silica (Mallet et al, 2013(Mallet et al, , 2015, (2) a pure gypsum sample (Brantut et al, 2012), and (3) a Plexiglas (PMMA) sample (e.g., Batzle et al, 2006). These samples were chosen because (1) they are homogeneous and isotropic media at the sample scale, (2) their static and dynamic elastic properties are known, and they show a large range in elastic moduli, (3) these samples have no porosity, and their elastic properties are not expected to change with confining pressure or added axial stress, and (4) although glass and gypsum elastic properties are independent of frequency, Plexiglas is a viscoelastic material whose elastic properties are frequency dependent.…”
Section: Calibration Samplesmentioning
confidence: 99%
“…Three standard samples were chosen to test the experimental setup and procedure: (1) a synthetic glass sample made of amorphous silica (Mallet et al, 2013(Mallet et al, , 2015, (2) a pure gypsum sample (Brantut et al, 2012), and (3) a Plexiglas (PMMA) sample (e.g., Batzle et al, 2006). These samples were chosen because (1) they are homogeneous and isotropic media at the sample scale, (2) their static and dynamic elastic properties are known, and they show a large range in elastic moduli, (3) these samples have no porosity, and their elastic properties are not expected to change with confining pressure or added axial stress, and (4) although glass and gypsum elastic properties are independent of frequency, Plexiglas is a viscoelastic material whose elastic properties are frequency dependent.…”
Section: Calibration Samplesmentioning
confidence: 99%
“…As in other materials, cracks in calcite can propagate subcritically in mode I [ Henry et al , ; Dunning et al , ; Røyne et al , ; Rostom et al , ], which leads to possible time dependence of brittle failure [ Johnson and Paris , ; Scholz , ; Kranz , ; Atkinson , ; Heap et al , ; Mallet et al , ] reviewed in Brantut et al []. Thus, limestones deformed under constant stress conditions can undergo brittle creep, as recently shown by Brantut et al [].…”
Section: Discussionmentioning
confidence: 74%
“…Ashby and Sammis [], Deshpande and Evans [], Bhat et al [], Brantut et al [], and Mallet et al [] among others showed that brittle creep can be modeled adequately by the propagation of wing cracks from initial monosized flaws, a geometry in good agreement with direct observations on limestone by Olsson []. Since subcritical crack growth is thermally activated, the growth of crack length ( l ) can be described using the law proposed by Darot and Guéguen [] and Mallet et al []: normaldlnormaldt=truel̇0exp()EakTexp[]skT()KI2E02γ, where truel̇0 is a characteristic crack speed dependent on the interatomic distance and atomic vibration frequency, E a is an activation energy, s is an elementary surface, k is Boltzmann's constant, T is temperature, K I is the stress intensity factor, and γ is the surface energy. Mallet et al [] showed that this crack growth law leads to an exponential relation between differential stress and strain rates, as described by equation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 (Ashby and Sammis 1990). This classical model is widely applied to study the micromechanical properties of brittle material (Deshpande and Evans 2008;Bhat et al 2011;Brantut et al 2012;Mallet et al 2015). The rock is assumed to be an isotropic elastic body that contains initial penny-shaped microcracks with radius a, and the angle between each initial microcrack and maximum principal stress r 1 is assumed to be u.…”
Section: Relationship Between Stress and Crack Growth In Compressionmentioning
confidence: 99%